The Determinant Factors Influencing the Competency of Science Teachers in Aceh Province, Indonesia - Muchsin Muchsin; M Yusuf; Mulyadi Mulyadi (Jurnal Penelitian Pendidikan IPA, 2025)
Teacher competence is one of the critical elements in the success of education in Indonesia. This study aims to analyze the determinant factors influencing the competence of science teachers in the Province of Aceh, Indonesia, with a focus on the impact of academic supervision, work motivation, and infrastructure facilities on teacher competence and its implications for organizational support. The research method employed is a quantitative approach using questionnaires and Structural Equation Modelling Partial Least Square (SEM-PLS) analysis. The research sample consists of 116 high school teachers from three districts in Aceh. The results indicate that academic supervision and infrastructure facilities have a significant influence on organizational support, while work motivation does not have a significant impact. Organizational support, in turn, has a positive and significant influence on teacher competence. These findings suggest that improving the quality of academic supervision and the availability of infrastructure facilities can enhance organizational support, which subsequently contributes to the improvement of teacher competence. This study provides practical contributions to the development of educational policies, particularly in supporting the enhancement of teacher competence through the optimization of supervision, motivation, and facilities.